2017
DOI: 10.1021/acs.jafc.7b03778
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Sensory Evaluation of Volatile Constituents of Fresh Blackcurrant (Ribes nigrum L.) Fruits

Abstract: Volatile constituents of fresh blackcurrant (Ribes nigrum L.) berries were isolated via vacuum-headspace extraction and analyzed by capillary gas chromatography-mass spectrometry. In agreement with previous studies with frozen fruits, short-chain esters and terpenes were major compound classes. However, rather high concentrations of C-compounds (e.g., (E)-hex-2-enal, (Z)-hex-3-enal) constituted a striking difference to data reported for frozen fruits. Frozen storage of blackcurrant berries was shown to result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…The impact of freezing on the volatile composition of blackcurrant was shown by Jung et al to be especially remarkable during the first 3 months of storage, whereas the composition was close to constant from that point onward. 12 Figure 2 depicts the total volatile contents in regard to storage time (i.e., total volatiles, Figure 2 A; hydrocarbons, Figure 2 B; and oxygenated monoterpenes, Figure 2 C). This effect is more apparent in ‘Mortti’ and ‘Ola’ than in ‘Melalahti’.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of freezing on the volatile composition of blackcurrant was shown by Jung et al to be especially remarkable during the first 3 months of storage, whereas the composition was close to constant from that point onward. 12 Figure 2 depicts the total volatile contents in regard to storage time (i.e., total volatiles, Figure 2 A; hydrocarbons, Figure 2 B; and oxygenated monoterpenes, Figure 2 C). This effect is more apparent in ‘Mortti’ and ‘Ola’ than in ‘Melalahti’.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have been devoted to characterizing the aroma compounds 13 as well as the impact of the cultivar, 14 ripening stage, 9 thermal 15 and enzymatic treatments, 16 and freezing. 12 Altogether, these studies have characterized a vast number of compounds as constituents of the volatilome of blackcurrants, including compounds of various chemical classes such as alcohols, aldehydes, esters, and terpenes. However, to the best of the authors’ knowledge, no research has been reported on the contribution of the harsh Nordic environment and associated meteorological data to the volatile contents and compositions in blackcurrant cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Research in the highly appreciated blackcurrant odor direction continued to inspire chemists since the last review [1] and can be divided into sulfurous and non-sulfurous directions.S ulfurous volatiles of various biogenetic origins are important aroma constituents of most ripe fruits.Due to their volatility,low concentration and limited stability,special skills are required for sample preparation and analysis in order to be able to detect such compounds.T hus,b yc areful vacuum headspace extraction of blackcurrant berries (Ribes nigrum L.), 5 could be identified as one of the constituents with the highest aroma activity (Figure 3). [19] Sarrioxane (6) [20] can be regarded as acyclic homologue of 5,just the same way as Oxane (8)isacyclic analogue of Corps Guava (7). Theo xathianes are weaker and less sulfury than the free thiols,a nd they exhibit additional herbal, green or minty connotations.F or 7 and 8,t he olfactorily preferred enantiomers exhibiting desirable fruity notes are those with the (R)-configuration at the sulfur-bearing carbon atom.…”
Section: Blackcurrant:non-sticky Elegancementioning
confidence: 99%
“…Several studies have been conducted concerning the nutritional profile of ripe blackcurrant fruit in relation to quality (Hancock et al, 2007; Nwankno et al, 2012; Vagiri et al, 2013; Mikulic-Petkovsek et al, 2015; Mattila et al, 2016; Woznicki et al, 2016; Jung et al, 2017), however, much less is known regarding the dynamics of fruit chemistry during development. Furthermore, little is known regarding the underlying molecular mechanisms and patterns of gene expression associated with phytochemical accumulation in blackcurrant fruit.…”
Section: Introductionmentioning
confidence: 99%